CORRELATION OF 5, 6, 7, 8-TETRAHYDROACRIDINE BASED SCAFFOLD INHIBITORY AGENTS FOR ALZHEIMER DISEASE. - VENKATESWARLU BOLISETTY; MANAIAH.V (International Journal of Pharma and Bio Sciences, 2013)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and one of the most common causes of dementia in the elderly. Acetylcholine sterase (AChe) inhibitors are the main drugs used in the treatment of AD. In this work, docking studies have been performed in order to understand the interaction between 5, 6, 7, 8-tetrahydroacridine inhibitor and AChe. The increase observed in the calculated binding affinities between inhibitor and AChe, reflect the experimental inhibitory activity expressed in terms of the half maximal inhibitory concentration (IC50 = 0.002 to 13.0 μm) of the above inhibitor. The AM1 and PM3 semi-empirical methods are used to estimate the predictive power of final QSAR equations. QSAR and molecular docking studies indicated that, 2-chloro, 9-amine derivative of 5, 6, 7, 8-tetrahydroacridine showed the highest percentage of concentration and can become a potential lead for treating Alzheimer’s disease.